The literary ballad in early nineteenth-century Russian literature - Katz, M (1972)
﻿ There is remarkably little research on the history of the Russian literary ballad or on its principal practitioner, V.A. Zhukovsky. This thesis is an attempt to rectify the situation: it follows the development of the ballad genre in Russian literature from its emergence in the 179Os to its demise in the 1840s. It has been decided to concentrate on the style of the ballads as the most original feature of the Russian genre, and in particular on the epithets in Zhukovsky's ballads as his most important contribution to the development of Russian poetic style. Consequently there will be no discussion of metrics, and only occasional remarks on syntax. Chapter I treats the relationship of the Russian literary ballad to the traditional folk genre, to the "ballad revival" in late eighteenth-century European literature, and to late eighteenth- century "pre-romantic" developments in Russian literature. The traditional folk ballad is defined in terms of its narrative unit, method, and attitude, and in terms of its intangible "world" or "code". Attempts by Russian collectors and critics to characterise the popular genre are also considered. Two examples of Russian folk ballads are analysed in order to demonstrate the constant features of the genre. The literary ballad is defined in terms of these same features, and its aesthetic principles are shown to be completely antithetical to those of the traditional genre. The impetus for the emergence of the Russian literary ballad was provided not by a desire to imitate the traditional genre, but rather by the Western European ballad revival. The English revival is traced froa the change in attitudes towards the folk genre as expressed by Sidney and Addison, to Prior's early literary imitation, to Percy's collection of texts, and finally to the literary ballads of Scott and Southey. Other authors which had some influence on the Russian movement (Thompson, Young, Gray, Macpherson's Ossian) are considered briefly. The German revival is similarly surveyed: Bürger's Lenore, Herder's pronouncements on folklore, and the literary ballads of Goethe, Schiller, and Uhland. The chapter concludes with a section on Russian "pre- romanticism", including anthologies of Russian superstitions, traditions, and skazki. as well as collections and imitations of folk songs and related genres - all of which influenced the development of the ballad. Chapter II, after a brief bibliography of the Russian literary ballad, examines several ballads published anonymously during the 1790s, including two written by Anna Turchaninova , and then analyses the literary ballads of M.N. Murav'ev, N.N. Karamzin, A.F. Merzlyakov, and I.I. Dmitriev. This analysis is followed by some general conclusions on the ballads of the 179Os. The literary ballad developed as a genre independent of folk poetry; the earliest Russian ballads were translations of English and German sources or reworkings of common European motifs. Love is the most common subject of the ballads, and the emphasis centres on the conventionally depicted characters, in particular on the psychology of the heroine. The settings are generalised, and parallels are often drawn between nature and the psychology of the characters. Attempts at local colour are minimal and unsuccessful. The structure of the ballads is relatively simple; authors frequently intrude into the action to comment on its significance. The style of the ballads of the 179Os is characterized by emotionalism in the form of hyperbole, exclamatory and interrogative syntax, and the frequency and choice of epithets. While eighteenth-century vocabulary and syntax tend to be used for the narrative, both the setting and psychology of the characters are usually described in "pre-romantic" language. Both Karamzin's Alina (179Os) and Merzlyakov's Milon (1797) contain a striking contrast between idyll and ballad, between classical and "pre-romantic" styles. Chapter III begins with a bibliographical sketch of biographical and critical studies on Zhukovsky, and with a note on the various editions of his work. It then examines Zhukovsky's theoretical statements about the ballad and compares them with contemporary descriptions of the genre. Both in his own opinion and in the testimony of his contemporaries, Zhukovsky was virtually identified as a balladnik. His choice of the literary ballad is attributed to the genre's popularity in Western European literature, and to the novelty of its exotic world. Zhukovsky's views on translation as expressed in his articles and letters are summarized: the translator is a creator, inspired by what he considers to be the ideal of the source, and seeking to create an effect on the reader equivalent to that produced by the original. As an example of this theory put into practice, Zhukovsky's ballad Rybak (1818) is compared with its source, Goethe's Der Fischer (1778). The sources of Zhukovsky's forty literary ballads are then enumerated, after which eight representative ballads are examined with reference to their subject, characters, setting, theme, and style. Lyudmila (18O8) established the pattern for Zhukovsky's ballads and introduced Bürger's theme into Russian literature; Svetlana (18O8-12) was written as a parody of Lyudmila; in Adel'stan (1813) Southey's ballad was given an original conclusion and a setting which became typical for all Zhukcvsky's ballads; in Ivikovy zhuravli (1813) Zhukovsky transformed Schiller's classical theme and created a mood of profound suspense; Eolova arfa (1814) combined the poet's favourite verbal motifs of youth, silence, and despondency; Gromoboi and Vadim (Dvenadtsat' spyashchikh dev) (1810-17) were written as a great parable of suffering and remorse, aspiration and fulfilment; finally, in Zamok Smal'gol'm (1822) Zhukovsky turned Scott's imitation of a popular ballad into a successful literary ballad. Throughout his career Zhukovsky never altered his choice of sources, his method of transforming European themes, or his individual Russian style. While the events of the original ballad source were usually retained in outline form, the characters were metamorphised into romantic heroes and heroines, whose speech was identical with that of the narrator. The settings were generalised and details of local colour were eliminated or Russianized. Zhukovsky's real theme always remained the same: his own experience of melancholy, anxiety, despair, love, fear, or resignation. The style which expressed this theme was always "literary": its originality resided in the alternating intonations, in the negative constructions, in the syntactical parallelism, and, more significantly, in the frequency, choice, and meaning of his epithets. In Chapter IV the epithets in Zhukovsky's ballads are studied. It begins with a summary of previous definitions of the epithet from Quintilian to the Russian Formalists. A definition is accepted which includes all purely descriptive words under the term "epithet", and allows for a distinction in usage or function. A.V. Isachenko's grammatical classification of adjectival epithets is adopted. After an evaluation of previous research on the epithet in Russian folk poetry, in English and German literary ballads, and in eighteenth-century Russian poetry, the following conclusions are drawn: firstly, there is little variety and no complexity in the epithets of Russian folk ballads - indeed, the range and use of the epithet is very limited; secondly, epithets in folk ballads differ fundamentally from those in literary ballads: the concrete, unambiguous epithets of the former are replaced in the latter by emotional, connotative epithets; thirdly, from its relatively insignificant role in the classical style of Lomonosov and Sumarokov, the epithet increases in importance in Russian poetry during the late eighteenth century. Murav'ev's language reflects the transition from objectivity to subjectivity, a trend which is continued by Karamzin and reaches its culmination in the poetry of Zhukovsky. Previous studies of Zhukovsky's epithets by G.A. Gukovsky and V.P. Petushkov are evaluated, and the results of a comprehensive examination of the sources and meanings of Zhukovsky's epithets are presented. There is no evidence to indicate any substantive relationship between the epithet in folk ballads and in Zhukovsky*s literary ballads. In comparison with the epithet in English and German ballads, Zhukovsky's epithets are more frequent, have their primary source in his own imagination, have fewer synonyms, and in their total subjectivity differ substantially in meaning. Zhukovsky's poetry undoubtedly emerges from the poetic practice of the eighteenth century; moreover his style was much influenced by late eighteenth-century developments. The originality of Zhukovsky's epithets lies firstly in their total subjectivity: they are employed not so much to describe objects and concepts, but rather to convey the poet's subjective impressions about these objects and concepts; and secondly, in the complex interrelationship between the applicability and indeterminateness of the epithets: as the applicability of an epithet increases, its meaning becomes more indeterminate; as the meaning becomes more indeterminate, so the applicability of the epithet increases. Zhukovsky's epithets created the foundation for the vocabulary of Russian romantic poetry. Therein lies his greatest contribution to the development of Russian poetic style. <p.chapter (batyushkov="" (shakhovskoi,="" 1815="" 1816;="" 1818,="" 1821.="" 1825="" 182o,="" a="" all="" analyzes="" and="" applicability="" assign="" attacks="" attempts="" attitudes="" ballad="" ballad.="" begins="" belinsky's="" between="" by="" chapter="" clarify="" comedy="" concludes="" confirm="" consideration="" considers="" creator,="" criticism="" development="" dispute="" epithets="" from="" genre="" gradual="" greatest="" griboedov="" help="" his="" imitators="" in="" innovations="" is="" it="" its="" joint="" katenin's="" katenin);="" language="" literary="" literature.<="" lyudmla="" made="" meaning="" nature="" next="" of="" ol'ga="" on="" originality="" over="" p="" places="" poetry,="" polemic="" polemics="" polevoi's="" praise="" pushkin="" relationship="" remarks="" resides.="" rightful="" russian="" rybak="" shift="" some="" surrounded="" that="" the="" their="" then="" these="" to="" traces="" treats="" v="" verse="" voeikov)="" which="" with="" work="" zagoskin,="" zhukovsky="" zhukovsky's="" zhukovsky,=""> In Chapter VI representative ballads by P.A. Katenin, A.I. Meshchevsky, and I.I. Kozlov are examined. Katenin was considered by contemporary critics as Zhukovsky's "opponent", and his ballads were said to be based on different stylistic principles. In fact, Katenin's contribution to the genre is shown to be ambiguous. While in Pevets (1814), Natasha (1814) and Pevets Uslad (1817) Zhukovsky's influence predominates, in Ubiitsa (1815), Leshii (1815), and Ol'ga (1816) Katenin was attempting to develop a new, more "popular" genre. Meshchevsky, an almost forgotten poet, has recently been discovered and labelled Zhukovsky's "double"; an analysis of his only two published ballads shows that while he imitated Zhukovsky's intonations, interrupted narrative, and epithets, his highly artificial images and complicated syntax tended to obscure his meaning. The ballads of Kozlov, Zhukovsky's most devoted disciple, are noteworthy for the originality of their narrative structure; but both their subjects and their style axe derived largely from Zhukovsky's ballads. Chapter VII treats Pushkin's literary ballads. It begins with a consideration of his early imitations of the subject, setting, characters, and style of Zhukovsky's ballads; Osgar (1814) an original poem based on an Ossianic theme, the early poslaniya, and several balladic lyrics are used to demonstrate in one way or another the influence of Zhukovsky's poetry. Next the chapter examines those works in which Pushkin parodied precisely those elements of Zhukovsky's ballads which he had previously imitated: Ten' Barkova (1814?), an unpublished pornographic parody of Gromoboi; Ruslan i Lyudmila (1817-2O), the fourth canto of which is a reworking of Vadim; and the balladic motifs in Tat'yana's dream in Onegin and in two of the Povesti Belkina. Finally Pushkin's original ballads are analyzed, and each is seen to be in some sense a "model": Rusalka (1819) is a reinterpretation of the nature-magic theme; Zhenikh (1825) synthesizes a German source and Russian folkloric motifs; Utoplennik (1828) places a popular motif and colloquial speech within the framework of sophisticated narration; Voron k voronu letit (1828) imitates the simplicity and unemotional realism of the traditional folk genre; and Besy (1830) is an exercise in the evocation of mood and the transformation of a ballad into a personal lyric. In his literary ballads Pushkin succeeded, where Zhukovsky had failed, in approaching the narrative unit, method, attitude, and "world" characteristic of the folk ballads. Chapter VIII examines Lermontov's literary ballads. It begins with his earliest experiments based on German and English sources, including two ballads entitled Gost' written in the early 1830s. Both the choice of models for imitation and the style of his early works reflect the strong influence of Zhukovsky's ballads. These experiments were followed by a series of parodies on the ballad genre and its practitioners: Nezabudka (183O), a comic reworking of Schiller's Der Taucher: On byl v krayu svyatom (1832), a parody of Zhukovsky's Staryi rytsar' (183O); and Yugel'skii baron (1837), a parody of Zhukovsky's Zamok Smal'gol'm. Beginning with his ballad cycle of 1832 (Trostnik, Rusalka, Ballada - Kuda tak provorno), Leratontov began to use the genre in a creative and individual way. In Tri pal'my (1S39) he reinterprets the theme of Pushkin's Podrazhanie Koranu IX. and introduces rich visual and aural imagery; in Dary Tereka (1839) he combines folk elements with literary motifs; in Spor (1841) the theme of man's destruction of natural beauty is presented in a series of vivid visual images; Tamara (1841), Lermontov's most original literary ballad, is another reworking of the nature-magic theme of Zhukovsky's Rybak and Pushkin's Rusalka: finally, Morskaya tsarevna (1841) is a reworking of Lermontov's own earlier Rusalka, with an engaging narrative and meaningful theme. Lermontov's literary ballads are neither "models" in the sense that Pushkin's are, nor do they approach the characteristics of the traditional folk genre: for Lermontov the literary ballad was merely one of the available lyrical forms, not the most fashioniable genre in Russian poetry. The conclusion includes a brief survey of the Russian literary ballad from the death of Lermontov to the Soviet period and the suggestion that any future history of the European ballad revival should consider other Slavonic literatures, in particular, the ballads of Mickiewicz, Shevchenko, and Erben. The appendixes include materials on the epithet in Russian folk ballads and in English and German literary ballads; on the epithet in Zhukovsky's ballads; on the epithet in Zhukovsky's ballad manuscripts; and on Zhukovsky's editions of Murav'ev and Kamenev. </p.chapter>